Kepuasan kerja tinggi pada mental workload yang tinggi: Studi korelasi di hotel â€œXâ€ - Nainggolan, Ellen Violetta; Hartika, Listiyani Dewi (Jurnal Psikologi Ulayat: Indonesian Journal of Indigenous Psychology, 2016)
The increasing amount of hotels in Bali may cause tougher competition among existing hotels. Human resources as organization activator will have an extra workload, such as increasing customer service quality and being an informal marketer. This situation can cause high mental workload felt by the staff. High mental workload is not always balanced by low job satisfaction, as with high mental workload can urge the staff to achieve higher performance and feel work satisfaction. Therefore, researcher wanted to intensively find out the relationship between mental workload and job satisfaction measured with scales designed by the researcher, interview and observation with 52 staff as samples. The result shows that there is a positive relationship between mental workload and job satisfaction (r = .688; p = 0.000). In other words, whenever mental workload is high, job satisfaction will also be high.